Business stakeholders role in sustainable water resource management in Jaffna district - Shivany, S.; Kumarendran, B.; Dilshani, V. (University of Jaffna, Sri Lanka, 2022)
Water security is a problem for many developing countries, and this is a life- threatening issue in Jaffna district, which is found in the catchment basin positioned in the areas that created water-related challenges. These continuous problems related to water security, in many places in the Jaffna peninsula, are faced with severe challenges in water resource management for sustainability in socio and economic development. This situation clearly demands new knowledge on how the key water stakeholder actors can contribute to managing water resources sustainably to bring about improved access to water. This would happen when all the water stakeholders act together through participatory involvement. The business sector is the major sector impacting the economic and social development of the country by practicing sustainable approaches and new strategies to manage water resources. Existing water-related problems are expected to increase, and conventional water resource management systems are not likely to face future challenges. There is a need for integrated water resources management, which should be participatory, technically and scientifically informed. Stakeholder involvement and their perspectives towards water management have a key role in water management, but simultaneously businesses play a major role in water management. The purpose of this paper is to explore the business stakeholder perspective on water management. To reach this goal, a participatory action research method was adopted, and data were collected from the business stakeholders in Jaffna district through a roundtable workshop approach. Thematic analysis was employed to identify the role of business stakeholders in sustainable water resource management. The empirical evidence obtained from this study shows water resource management problems such as drinking water problems, incompetent wastewater treatment, water supply-related issues and ineffective water resource management. Further, from the business stakeholders’ perspectives, it is clear that the ‘operational water resource management’ has been perceived as the collective responsibility of multi-stakeholder groups. This operational water resource management involved with the business sector must be administrated with the planned action to control the water-related challenges. This study contributes to the existing research about water management, which can have the ability to develop integrated business-stakeholder participation to minimize water-related problems in Jaffna. From the practical viewpoint, the study has found that water resource management is based on networking with the business as well as other stakeholders to build and support water management, and it is associated with reducing water contamination, rainwater harvesting, water treatment, creating awareness among the businesses and consumers and water quality testing during the business operations. The study outlined the existing contribution of the business stakeholders in water resource management and water-related issues and proposed sustainable water resource management from the business stakeholders’ perspective for further investigation and development of an approach in the Jaffna district. This addressed fact represents the primary contribution of the study.
Keywords: Business stakeholders; Sustainable water resource management; Participatory action research; Jaffna